Tracking the Money for Open Educational Resources in South African basic Education: What We Don’t Know - Sarah Goodier (Athabasca University Press, 2017)
Limited research has been done to date on the extent of public funding of Open Educational Resources (OER) within basic education (K-12 equivalent) in South Africa. As claims have been made about the potential cost reductions that come with using OER, this study aimed to establish a benchmark of public spending on educational resources, uncover how much is being spent on OER and assess cost-savings of OER adoption. A desk review and document analysis of official information sources on South African basic education was conducted to develop a conceptual understanding of funding allocations the South African government uses for educational resources. A review of publicly available government reports and budgets showed that there is insufficient information at this time to determine how much is being spent on OER specifically or to act as a benchmark for potential cost savings of OER. This study highlights the information gaps which would need to be filled in order to make claims about OER and their potential as cost savers.